Using Peer Tutoring Method on English Language Learning at Sman 10 Pandeglang - Nurlita; Gumelar, Rizdki Elang; Munawaroh , Tatu (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2024)
Peer Tutoring method is an active learning method and focuses on students. This research aims to analyze Peer Tutoring Method in Learning. This research used a qualitative approach with a content analysis design. This research used triangulation of data collection methods involving observation, interview, and documentation. Data was obtained from observation. Interview were conducted at the twelfth grade which consist of 5 students and one English teacher. Documentation was done by captured teaching and learning activities on Peer Tutoring method. Data analysis was conducted to analyze important findings in accordance with the research objectives. This findings show that first, the used of Peer Tutoring method in English Language Learning can help students to play an active role in participating in the learning process. Based on the findings of this research, Peer tutoring method in terms of the learning process is in accordance with the stage of the learning in general stages. Second, In Learning outcomes based on the cognitive, affective, and psychomotor domains as a whole, it is difficult to run well and in accordance with the intended learning outcomes. Third, In supporting factors, students are able to play an active role in carrying out the learning process. Teacher should better to identify the problems that become such obstacles. This finding also expects other researcher to analyze or maximize this method in English Language Learning.